Multiple causes of an unexpected malaria outbreak in a high-transmission area in Madagascar. (December 2016) - Kesteman, Thomas; Rafalimanantsoa, Solofoniaina; Razafimandimby, Harimahefa; Rasamimanana, Heriniaina; Raharimanga, Vaomalala; Ramarosandratana, Benjamin; Ratsimbasoa, Arsene; Ratovonjato, Jocelyn; Elissa, Nohal; Randrianasolo, Laurence; Finlay, Alyssa; Rogier, Christophe; et al.
Abstract Background The malaria burden in Madagascar dropped down last decade, largely due to scale-up of control measures. Nevertheless, a significant rise of malaria cases occurred in 2011–2012 in two regions of the rainy South-Eastern Madagascar, where malaria is considered as mesoendemic and the population is supposed to be protected by its acquired immunity againstPlasmodium . A multidisciplinary investigation was conducted in order to identify the causes of the outbreak. Methods In March 2012, a cross-sectional study was conducted in 20 randomly selected clusters, involving the rapid diagnostic testing of all ≥6 month-old members of households and a questionnaire about socio-demographic data and exposure to malaria control interventions. Changes in environmental conditions were evaluated by qualitative interview of local authorities, climatic conditions were evaluated by remote-sensing, and stock outs of malaria supplies in health facilities were evaluated by quantitative means. Two long-lasting insecticidal nets (LLINs) were sampled in each cluster in order to evaluate their condition and the remanence of their insecticidal activity. The entomological investigation also encompassed the collectionAnopheles vectors in two sites, and the measure of their sensitivity to deltamethrin. Results The cross-sectional survey included 1615 members of 440 households. The meanPlasmodium infection rate was 25.6 % and the mean bed net use on the day before survey was 71.1 %. The prevalence ofPlasmodium infections was higher in 6–14 year-old children (odds ratio (OR) 7.73 [95 % CI 3.58–16.68]), in rural areas (OR 6.25 [4.46–8.76]), in poorest socio-economic tercile (OR 1.54 [1.13–2.08]), and it was lower in individuals sleeping regularly under the bed net (OR 0.51 [0.32–0.82]). Stock outs of anti-malarial drugs in the last 6 months have been reported in two third of health facilities. Rainfalls were increased as compared with the three previous rainy seasons. Vectors collected were sensitive to pyrethroids. Two years after distribution, nearly all LLINs collected showed a loss of physical integrity and insecticide activity, Conclusions Increased rainfall, decreasing use and reduced insecticide activity of long-lasting insecticide-treated nets, and drug shortages may have been responsible for, or contributed to, the outbreak observed in South-Eastern Madagascar in 2011–2012. Control interventions for malaria elimination must be sustained at the risk of triggering harmful epidemics, even in zones of high transmission.